American media, Scandinavian audiences: Contextual fragmentation and polarisation among Swedes and Norwegians engaging with American politics - Robinson Jessica Yarin (Nordicom Review)
This article explores the contextual nature of fragmentation and polarisation – subjects that have attracted significant concern in the age of social media. I investigate the media sharing practices of Scandinavian Twitter users discussing the 2020 American presidential election, an event that attracted international attention. Using links in tweets, I map the media networks of users in Sweden and Norway in their national languages and in English. This intranational approach provides a view into whether fragmentation and polarisation are characteristic of the audience or the media milieu. The findings show Scandinavian users exhibit low audience polarisation within their national languages, but they display polarisation similar to American users when engaging with English-language media. At the same time, media fragmentation is higher in the Norwegian language than in any other sphere. This article sheds light on the relationship between the sometimes-conflated concepts of fragmentation and polarisation and provides a discussion of the implications of political information sharing on transnational digital platforms.